2020
DOI: 10.1242/dmm.045641
|View full text |Cite
|
Sign up to set email alerts
|

An HIV-Tat inducible mouse model system of childhood HIV-associated nephropathy

Abstract: Background: Modern antiretroviral therapies (ART) have decreased the prevalence of HIV-associated nephropathy (HIVAN). Nonetheless, we continue to see children and adolescents with HIVAN all over the world. Furthermore, once HIVAN is established in children, it is difficult to revert its long-term progression, and we need better animal models of childhood HIVAN to test new treatments.Objectives. To define whether the HIV-1 trans-activator (Tat) gene precipitates HIVAN in young mice, and to develop an inducible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…These findings are in agreement with the notion that other viral proteins and heparin-binding growth factors that are involved in the pathogenesis of HIVAN (e.g. Nef, Tat, VEGF-A) ( He et al, 2004 ; Das et al, 2016 ; Korgaonkar et al, 2008 ; Tang et al, 2020 ) also activate the pERK pathway and can act in synergy with FGF-2 ( Seghezzi et al, 1998 ). Nonetheless, PD170374 did not completely normalize the proteinuria or completely reverse the renal histological lesions in HIV-Tg 26 mice injected with rAd-FGF-2 vectors.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with the notion that other viral proteins and heparin-binding growth factors that are involved in the pathogenesis of HIVAN (e.g. Nef, Tat, VEGF-A) ( He et al, 2004 ; Das et al, 2016 ; Korgaonkar et al, 2008 ; Tang et al, 2020 ) also activate the pERK pathway and can act in synergy with FGF-2 ( Seghezzi et al, 1998 ). Nonetheless, PD170374 did not completely normalize the proteinuria or completely reverse the renal histological lesions in HIV-Tg 26 mice injected with rAd-FGF-2 vectors.…”
Section: Discussionsupporting
confidence: 91%
“…In support of these findings, the HIV-Tat protein can interact with the extracellular domain of the Notch receptors and was suggested as a non-canonical ligand for Notch activation [50][51][52][53] . In addition, previous studies in HIV-Tg26 mice and human podocytes showed that HIV-1 can precipitate the development of HIVAN and affect the cytoskeletal structure of podocytes cultured from children with HIVAN 54,55 . Moreover, there are two RBP-JK binding sites adjacent to the NFÎşB binding sites on the HIV-LTR promoter.…”
Section: Discussionmentioning
confidence: 96%